Human Resource Management Strategy in Improving Employee Productivity at PT Panarub Industry Tangerang - Murniadi; Anita Ardiyanti (PDPI (Perkumpulan Dosen Peneliti Indonesia), 2025)
This study aims to examine and analyze the human resource management (HRM) strategies implemented to improve employee productivity. The research focuses on key HR elements such as workforce planning, recruitment and selection, training and development, and performance evaluation systems. A qualitative research approach was adopted using data collection techniques including observation, in-depth interviews, and document analysis. The findings reveal that well-planned and continuous HRM strategies positively impact employee productivity. Ongoing and relevant training programs, objective performance assessments, and motivational approaches through career development and recognition have been shown to enhance employee morale and efficiency. This study recommends integrating HR strategies with broader organizational goals to develop professional, competent, and competitive human resources.